Fungal communities isolated from dead apple leaves from orchards in Quebec - Bernier, J.; Carisse, O.; Paulitz, T.C. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1996)
Venturia inaequalis, the causal agent of apple scab, overwinters in apple (Malus pumila) leaves on the orchard floor by producing pseudothecia. The objectives of this survey were to make a collection of fungi to be subsequently tested for their potential as psychrophile biocontrol agents against V. inaequalis and to acquire knowledge on the diversity of the microflora of dead apple leaves. Fungi were recovered from dead apple leaves collected in the spring and fall of 1993. A total of 345 isolates from 49 genera were identified. Fifteen gene were not previously recorded as colonizers of apple leaves in North America.